Screening of Salt-Tolerant Thinopyrum ponticum Under Two Coastal Region Salinity Stress Levels - Tong, Chunyan; Yang, Guotang; AoenBolige,; Terigen,; Li, Hongwei; Li, Bin; Li, Zhensheng; Zheng, Qi (Frontiers in Genetics, 2022)
To accelerate the exploitation and use of marginal soils and develop salt-tolerant forage germplasm suitable for the coastal regions of China, seven lines of decaploid tall wheatgrass [Thinopyrum ponticum (Podp.) Barkworth and D. R. Dewey, 2n = 10x = 70] were transplanted under low (.3%) and high (.5%) salt conditions for a comprehensive analysis at the adult-plant stage. Differences were observed among these materials, especially in terms of grass yield, agronomic characteristics, and physiological and biochemical indices. Line C2 grew best with the highest shoot total fresh and dry weights under all conditions except for the milk-ripe stage in Dongying in 2019. The total membership value of C2 also reflected its excellent performance after transplanting. As superior germplasm, its relatively high antioxidant enzyme activities and chlorophyll a/b ratio suggested C2 may maintain normal metabolic and physiological functions under saline conditions. Furthermore, decaploid tall wheatgrass as a forage grass species has a high nutritive value beneficial for animal husbandry. Accordingly, line C2 may be used as excellent germplasm to develop salt-tolerant cultivars in the Circum-Bohai sea.